The Microbiota Profile Analysis of Combined Periodontal-Endodontic Lesions Using 16S rRNA Next-Generation Sequencing - Ping Sun; Zhiyong Guo; Daiping Guo; Jian Wang; Tingting Wu; Tingjun Li; Jiannan Liu; Xinhua Liu (Journal of Immunology Research)
Objective. The primary aim of this investigation was to analyze the microbiome in patients with combined periodontal-endodontic lesions. Method. Patients with loose and/or painful teeth referred for treatment from March 2020 to December 2020 in the First People’s Hospital of Jinzhong were recruited. Samples were collected from teeth diagnosed as chronic periodontics (PE), ulcerative pulpitis (PU), and retrograde pulpitis (RE). Genomic DNA was extracted. The quantitative polymerase chain reaction, targeting the 16S ribosomal RNA (rRNA), was adopted for the quantification of bacteria. Then, the V3-V4 hypervariable regions of the 16S rRNA gene were amplified and subjected to next-generation sequencing. The statistical analysis was performed by R software (V3.5.1). Results. A total of 57 qualified samples were collected from 48 patients and analyzed (7 PE, 21 PU, and 19 RE). By linear discriminant analysis effect size, Kingella and Barnesiella were significantly increased in the periodontal pocket of retrograde pulpitis (RE-PE), compared with PE. The relative abundance of Clostridiales Incertae Sedis XI, Fusobacteriaceae, Fusobacterium, Parvimonas, Micrococcaceae, and Rothia was significantly increased in the pulp of retrograde pulpitis (RE-PU) than PU and RE-PE. Prevotella, Leptotrichia, Porphyromonas, Streptococcus, and Fusobacterium are consistently at a high abundance, across PU, RE-PE, and RE-PU. Conclusion. The current study highlighted the evidence that a specific microbial community is associated with the occurrence of retrograde pulpitis. The microenvironment of the root canal and pulp chamber will select microbiota. This study offered insights into the pathogenesis of retrograde pulpitis.